PERANCANGAN COMPANY PROFILE CV. AYAH DALAM BENTUK BOOKLET - ARIF RAHMAN, Drs. Syafwan, M.Si, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Cv.Ayah is a transportation company who has a lot of the bus operates but only just. Cv.Ayah is a pioneer in a bus for routes payakumbuh-padang patas.Cv. Ayah never have promotion and just rely on a board a brand that being in each the counter, because it is to the media through a booklet. The purpose of design of this is to inform the target audience about cv.Ayah so that the target audience vote CV, Ayah as a means of transportation.Kata Kunci : Booklet, Companany Profile, promosi, CV.AYAH